Comparison of Nurse Work Hours and Nursing Activities Between High‐ and Low‐Staffed General Wards: A Cross‐Sectional Study - Jiyeong Seong; Sung‐Hyun Cho; Hyo‐Jeong Yoon; Won‐Hee Sim; Moon‐Sook Kim (Nursing Open)
ABSTRACT Aim To compare nurse work hours and nursing activities between high‐staffed and low‐staffed general wards to examine the effects of increased staffing on nurse workload and nursing care. Design A secondary analysis was conducted using cross‐sectional data collected at a tertiary teaching hospital in South Korea in January 2020. Methods Nursing activities provided by 350 nurses were observed every 10 min during their shifts for three observation days in four high‐ and four low‐staffed wards. Nurse‐to‐patient ratios, nurse work hours, nursing activities and the composition of nursing hours (direct care, indirect care and associated work) were analysed. Results After excluding non‐productive personal time, nurses in the low‐staffed wards worked 9.28 h, which indicates 1.28 h of overtime work on average, while the high‐staffed wards recorded 7.90 h of productive work time. The nurse‐to‐patient ratio in the high‐staffed wards was 1:4.73, whereas that in the low‐staffed wards was 1:8.87. The proportion of direct care hours out of nurse work hours was higher in the low‐staffed wards (30.9%) than in the high‐staffed wards (25.7%). Nurses in the low‐staffed wards provided a greater number of direct care hours, and the largest difference in direct care hours between the two groups was found on night shifts. Nurses in the high‐staffed wards spent more time communicating with patients and charting, whereas nurses in the low‐staffed wards spent more time on vital signs and medications. Conclusion Improved staffing had positive impacts on patients and nurses. Patients benefited from better staffing through increased communication with nurses. Better staffing also reduced overtime work and activities conducted during night shifts. Implications for the Profession and Patient Care Adequate staffing is essential to improve patient care quality and reduce nurse workload. Nursing activities must be prioritised and redesigned to maximise the benefits of increased staffing on patient and nurse outcomes. Reporting Method We have adhered to the STROBE reporting guidelines. No Patient or Public Contribution The aim of this study was to compare nurse work hours and nursing activities between high‐staffed and low‐staffed wards.